2015
DOI: 10.1016/j.avsg.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day Outcome of Delayed Versus Early Management of Symptomatic Carotid Stenosis

Abstract: During the study period, the reduction of the symptom-to-knife time in application to the carotid revascularization guidelines did not impact our outcomes suggesting that early CEA achieves 30-day mortality and morbidity rates at least equivalent to those of delayed CEA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…В работе E. Charmoille и соавт. [16] проанализированы результаты ранней (1-14 сут, в среднем 9,3 сут) и отсроченной (более 14 дней) КЭЭ у пациентов с симптомными стенозами. Тридцатидневный показатель «инсульт+летальность» в группе ранней реконструкции ВСА составил 1,7% против 3,5% в группе отсроченной КЭЭ, в те же сроки по- Анализ результатов хирургического лечения пациентов, оперированных в сроки до 20 сут от момента ишемического события, продемонстрирован в работе A. Ivkošić и соавт.…”
Section: результаты и обсуждениеunclassified
“…В работе E. Charmoille и соавт. [16] проанализированы результаты ранней (1-14 сут, в среднем 9,3 сут) и отсроченной (более 14 дней) КЭЭ у пациентов с симптомными стенозами. Тридцатидневный показатель «инсульт+летальность» в группе ранней реконструкции ВСА составил 1,7% против 3,5% в группе отсроченной КЭЭ, в те же сроки по- Анализ результатов хирургического лечения пациентов, оперированных в сроки до 20 сут от момента ишемического события, продемонстрирован в работе A. Ivkošić и соавт.…”
Section: результаты и обсуждениеunclassified
“…More recent trials show that carotid revascularization performed within 15 days after symptom onset versus delayed CEA in symptomatic patients have no difference in outcomes. 48 A 2009 systematic review showed that the rate of perioperative stroke or mortality is significantly higher in emergent CEA (14.0%) compared with nonemergent CEA (4.0%). 49 Studies suggest that urgent CEA can be safely performed in symptomatic patients to improve neurologic outcome 50 without increased procedural risk, 51 although the poorest outcomes occur in patients with an evolving stroke, and urgent CEA should be offered with caution in these patients, 52 and can perhaps be offered within 48 hours after TIA or SIE to prevent recurrent stroke.…”
Section: Symptomatic Carotid Artery Stenosismentioning
confidence: 99%